Pergamon, Türkei. Die Arbeiten des Jahres 2017 - Pirson, Felix; Emme, Burkard; Erkul, Ercan; Feuser, Stefan; Laufer, Eric; Mania, Ulrich; Meinecke, Matthias; Mecking, Rebekka; Rabbel, Wolfgang; Tezer-Altay, Seçil (e-Forschungsberichte des DAI, 2018)
The work of the Pergamon excavation in 2017 concentrated on the exploration of the Hellenistic residence city and its surroundings within the framework of the current research programme, whose field work could be completed. The focus was on geophysical prospections and stratigraphic trenches on the burial mound Yığma Tepe. To test hypotheses on the development of the settlement history of the city hill of Pergamon, Bau X on the western slope was examined. The survey of the Kane-peninsula was finished; it provided unexpected insights into the importance of the site for traffic and trade in the microregion. The extensive monument preservation measures at Pergamon concentrated on the Gymnasion and the Red Hall. A detailed preliminary report, which contains also information about other fields of activity such as the study of elite burial practises, will be published in “Archäologischer Anzeiger” 2018/2.